2022
DOI: 10.1371/journal.pone.0263285
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitor dapagliflozin prevents atherosclerotic and cardiac complications in experimental type 1 diabetes

Abstract: Introduction Cardiovascular disease (CVD) is two to five times more prevalent in diabetic patients and is the leading cause of death. Therefore, identification of novel therapeutic strategies that reduce the risk of CVD is a research priority. Clinical trials showed that reduction in the relative risk of heart failure by sodium-glucose cotransporter 2 inhibitors (SGLT2i) are partly beyond their glucose lowering effects, however, the molecular mechanisms are still elusive. Here we investigated the role of SGLT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…In a recent study conducted by Hodrea et al [ 64 ], the group of investigators demonstrated that dapagliflozin ameliorates cardiac inflammation induced by diabetes mellitus similarly to the effect observed in type 2 diabetic rodent models by Aragón-Herrera et al [ 117 ] or Ye et al [ 118 ]. The anti-inflammatory and anti-fibrotic effect of dapagliflozin was also evidenced in the study proposed by the last mentioned investigators, dapagliflozin administration leading to decreased inflammasome activation and decreased levels of IL-1β [ 118 ].…”
Section: Effects Of Sglt2 Inhibitors On Vascular Agingmentioning
confidence: 87%
See 2 more Smart Citations
“…In a recent study conducted by Hodrea et al [ 64 ], the group of investigators demonstrated that dapagliflozin ameliorates cardiac inflammation induced by diabetes mellitus similarly to the effect observed in type 2 diabetic rodent models by Aragón-Herrera et al [ 117 ] or Ye et al [ 118 ]. The anti-inflammatory and anti-fibrotic effect of dapagliflozin was also evidenced in the study proposed by the last mentioned investigators, dapagliflozin administration leading to decreased inflammasome activation and decreased levels of IL-1β [ 118 ].…”
Section: Effects Of Sglt2 Inhibitors On Vascular Agingmentioning
confidence: 87%
“…Until the development of SGLT2 inhibitors, glucose-lowering agents had little or no impact on CVD progression in patients with diabetes mellitus [ 64 ]. Of all the agents in this class, dapagliflozin is the only one approved for the treatment of patients with type 1 diabetes in the European Union to date [ 64 ].…”
Section: Effects Of Sglt2 Inhibitors On Vascular Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the molecular mechanisms are still unclear ( 42 ). This gap is mainly due to the absence of evidence showing SGLT2 expression in monocytes/macrophages and endothelial cells.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…SGLT2 inhibitors may indeed influence the blood lipid profiles. Many studies have investigated their role in atherosclerosis (41)(42)(43), triglyceride levels (44), and nonalcoholic fatty liver disease (45,46). A meta-analysis of 15 randomized trials (with a total of 7,578 patients with type 2 diabetes mellitus) found an increase in total cholesterol, lowdensity lipoprotein cholesterol, and high-density lipoprotein cholesterol, while a decrease in triglycerides with SGLT2 inhibitors compared to placebo or other oral glucose-lowering drugs.…”
Section: Safety Of Sglt Inhibitorsmentioning
confidence: 99%